(3GdSQGFQ GdMGhj dJMQjQ GdaJGhjs - (3GdYLdj GdMdj, eMeO Hf efUhQ Hf CMeO Hf EOQjS, J (B598(3g` (B1202(3es ((3YHO GdcQje Hf Uaj GdOjfs)
(3ChdgG (B:s
(3ChdgG(B: (3GdMeO ddg GdPj Ndb GdEfSGf aYOdg (B... (3CeG HYO, aEf Gdabg CLed eG GdJMbJg Gdgeg hYQaJg gPg GdCeI (B...s
(3BNQgG (B:s
(3BNQgG(B: (3jJCedhg hdPdc RGO GdeJCNQhf Ydi GdeJbOejf hbO cKQJ GdYdhe HcKQI GdQLGd hGJUGd GdReGf hGeJOGO GdBLGd hQHeG de jTHY Gdbhd GdeJbOe aj GdeSCdI YdjgGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf, L (B3: 734s
(3GdPQjYI, L (B12: 112s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis